DEALING WITH UNCONTROLLED SEIZURE IN CATAMENIAL EPILEPSY: A CASE REPORT - Machlusil Husna; I Wayan Arsana Wiyasa; Ria Damayanti; Syah Sembung Wasiso; Fahimma Fahimma; Kartika Agustina (MNJ (Malang Neurology Journal), 2023)
Catamenial epilepsy refers to a seizure pattern that coincides with the menstrual period. Patients with catamenial epilepsy often leads to intractable epilepsy and may have an adverse impact on quality of life. Several medications are the therapeutic options, however, there is uncertainty regarding the best treatment, and these medications often fail to control the seizure. This makes catamenial epilepsy categorized as pharmaco-resistant epilepsy. This paper reported a case of perimenstrual catamenial epilepsy with an uncontrolled seizure problem. Seizures still occur with optimal management, and thereby clinicians must continue to re-evaluate clinical conditions and treatment selection to achieve optimal management. Personalized-based treatment should be considered in catamenial epilepsy management. This report discusses the challenges of catamenial epilepsy, understanding the catamenial process, and dealing with the problem with a practical personalized approach.